Evaluation of feasibility and acceptability of a web-based diabetes prevention program (DPP) for diabetes risk reduction in Chinese Americans in New York City - Yeh, Ming-Chin; Lau, Wincy; Keady, Claire Anselmo; Horlyck-Romanovsky, Margrethe; Tung, Ho-Jui; Hu, Lu; Ma, Grace X.; Wylie-Rosett, Judith (Frontiers in Public Health, 2023)
Intensive lifestyle intervention remains an effective modality to reduce diabetes incidence and delay the progression to type 2 diabetes. The primary aim of this study was to pilot-test the feasibility and acceptability of a culturally and linguistically tailored web-based DPP intervention among Chinese Americans with prediabetes living in New York City. Thirteen Chinese American participants with prediabetes were recruited to complete a 1-year web-based Diabetes Prevention Program (DPP) lifestyle intervention. Quantitative and qualitative measures such as retention rate and data collected from web-based questionnaires and focus groups were collected and analyzed to assess study feasibility and acceptability. Participants were receptive to the program through high engagement, retention and satisfaction. Retention rate was 85%. 92% of participants completed at least 16 sessions out of 22 sessions. Post-trial surveys indicated high satisfaction of 27.2/32 based on Client Satisfaction Questionnaire (CSQ-8) score. Participants expressed the program increased their knowledge and methods to prevent onset of type 2 diabetes such as incorporating healthy eating habits and increasing physical activities. Although not a primary outcome, there was a significant weight reduction of 2.3% at the end of month 8 of the program (p<0.05). The culturally and linguistically adapted DPP via online platform successfully demonstrated feasibility and acceptability among Chinese Americans with prediabetes. Further evaluation of the web-based Chinese Diabetes Prevention Program in a larger trial is warranted.